2015
DOI: 10.1186/s13148-015-0166-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100 and microRNA-21 as markers of survival and chemotherapy response in pancreatic ductal adenocarcinoma UICC stage II

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) remains a highly chemoresistant tumor entity for which no reliable molecular targets exist to predict or influence the success of chemotherapy. Recently, we identified a panel of microRNAs associated with induced gemcitabine chemoresistance in human PDAC cell lines. This clinical study evaluates these microRNAs and associated molecular markers as prognostic markers of outcome in 98 PDAC patients Union Internationale Contre le Cancer (UICC) stage II undergoing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 37 publications
(35 reference statements)
1
36
1
Order By: Relevance
“…In essence, over 10% of all reported research findings of miRNA influences in cancer chemoresistance demonstrated that such a phenotype modulation was effected through simultaneous dysregulation of multiple miRNAs, rather than an individual putative chemoresistance miRNA—though no specific miRNA combination was identified as most prevalent by the authors [44,46,47,48,49,62,67,71,76,81,85,88,132,133,158,168,201,203,211,212,213,217,223,224,228,230]. This suggests that miRNA influences on cellular functions also occur at a more complex level, whereby it is a signature dysregulated expression pattern of two (or more) miRNAs that trigger simultaneous downregulation of a specific set of target transcripts leading to an ultimate change in cellular/tissue phenotype.…”
Section: Influences Of Mirnas In Cancer Chemoresistancementioning
confidence: 99%
“…In essence, over 10% of all reported research findings of miRNA influences in cancer chemoresistance demonstrated that such a phenotype modulation was effected through simultaneous dysregulation of multiple miRNAs, rather than an individual putative chemoresistance miRNA—though no specific miRNA combination was identified as most prevalent by the authors [44,46,47,48,49,62,67,71,76,81,85,88,132,133,158,168,201,203,211,212,213,217,223,224,228,230]. This suggests that miRNA influences on cellular functions also occur at a more complex level, whereby it is a signature dysregulated expression pattern of two (or more) miRNAs that trigger simultaneous downregulation of a specific set of target transcripts leading to an ultimate change in cellular/tissue phenotype.…”
Section: Influences Of Mirnas In Cancer Chemoresistancementioning
confidence: 99%
“…However, few studies have focused on the effect of Gem therapy on the metastasis of pancreatic cancer in vivo . Moreover, in studies that reported a combination therapy using ASO‐miR‐21 and Gem, most of them gave the two agents separately in different drug delivery systems . There were many disadvantages of using two drug carriers, including different biocompatibility and biodistribution, increased drug toxicity, and decreased drug combination activity.…”
mentioning
confidence: 99%
“…Moreover, in studies that reported a combination therapy using ASO-miR-21 and Gem, most of them gave the two agents separately in different drug delivery systems. (10,11) There were many disadvantages of using two drug carriers, including different biocompatibility and biodistribution, increased drug toxicity, and decreased drug combination activity. The lack of efficient delivery vectors hampered the clinical application of gene therapy.…”
mentioning
confidence: 99%
“…Furthermore, different miRs were described as prognostic markers: low miR‐192, high miR‐196a‐2, and low miR‐335 are unfavorable factors for patient's prognosis, while high levels of miR‐200c were associated with significantly better survival rates . Recently, we could identify miR‐21 and miR‐100 as unfavorable prognostic factors markers for overall survival and chemotherapy response in adjuvant‐treated PDAC UICC stage II patients . Correspondingly to the fact that many epigenetic molecules are involved in pathways that lead to PDAC drug resistance Ma et al .…”
Section: Epigenetic Regulation Of Epithelial‐to‐mesenchymal Transitiomentioning
confidence: 97%
“…101,102 Recently, we could identify miR-21 and miR-100 as unfavorable prognostic factors markers for overall survival and chemotherapy response in adjuvant-treated PDAC UICC stage II patients. 103 Correspondingly to the fact that many epigenetic molecules are involved in pathways that lead to PDAC drug resistance Ma et al highlighted the important role of miR-223 in gemcitabine resistance 104 while miR-320a promotes 5-FU resistance. 105 The crucial step in management of PDAC after diagnosis is therapy.…”
Section: Mini Reviewmentioning
confidence: 99%